TIGIT-Fc as a Potential Therapeutic Agent for Fetomaternal Tolerance - Fu, Wenyan; Cai, Renfei; Ma, Zetong; Li, Tian; Lei, Changhai; Zhao, Jian; Hu, Shi (Frontiers in Immunology, 2021)
The perfect synchronization of maternal immune-endocrine mechanisms and those of the fetus is necessary for a successful pregnancy. In this report, decidual immune cells at the maternal-foetal interface were detected that expressed TIGIT (T cell immunoreceptor with Ig and ITIM domains), which is a co-inhibitory receptor that triggers immunological tolerance. We generated recombinant TIGIT-Fc fusion proteins by linking the extracellular domain of TIGIT and silent Fc fragments. The treatment with TIGIT-Fc of human decidual antigen presenting cells (APCs), the decidual dendritic cells (dDCs) and Decidual macrophages (dMϕs) increased the production of interleukin 10 and induced the decidua APCs to powerfully polarize the decidual CD4+ T cells towards a classic TH2 phenotype. We further proposed that Notch signalling shows a pivotal effect on the transcriptional regulation in decidual immune cell subsets. Moreover, The administration of TIGIT-Fc to CBA/J pregnant mice at preimplantation induced CD4+ forkhead box P3+ (Foxp3+) regulatory T cells and tolerogenic dendritic cells and increased pregnancy rates in an abortion-prone animal model stress. The results suggested the therapeutic potential of the TIGIT-Fc fusion protein in reinstating immune tolerance in failing pregnancies.